Bivalent GAD autoantibody ELISA improves clinical utility and risk prediction for adult autoimmune diabetes. Issue 4 (23rd January 2023) - Kawasaki, Eiji; Shimada, Akira; Imagawa, Akihisa; Abiru, Norio; Awata, Takuya; Oikawa, Yoichi; Osawa, Haruhiko; Kawabata, Yumiko; Kozawa, Junji; Kobayashi, Tetsuro; Takahashi, Kazuma; Chujo, Daisuke; et al.
Abstract: Aim/Introduction: To investigate the differences in the clinical significance and glutamic acid decarboxylase autoantibody (GADA) affinity between RIA (RIA‐GADA) and ELISA (ELISA‐GADA) in patients with type 1 diabetes. Methods: A total of 415 patients with type 1 diabetes were enrolled, including 199 acute‐onset type 1 diabetes, 168 slowly progressive type 1 diabetes (SPIDDM), and 48 fulminant type 1 diabetes. GADA affinity was measured by a competitive binding experiment using unlabeled recombinant human GAD65 protein, and the diagnostic performance of both assays and the relationship between GADA affinity and the decline of fasting C‐peptide (F‐CPR) were examined. Results: While the ELISA‐GADA displayed a higher sensitivity than the RIA method in diagnosing type 1 diabetes in acute‐onset patients, about 40% of SPIDDM patients with low‐titer RIA‐GADA were determined as negative by the ELISA method. Patients with type 1 diabetes with RIA‐GADA alone had an older age of onset, less diabetic ketoacidosis, a higher BMI, and a higher F‐CPR compared with patients positive for both RIA‐GADA and ELISA‐GADA. Additionally, 36% of RIA‐GADA‐positive patients had low‐affinity GADA (<10 10  L/mol), which was significantly higher than in the ELISA‐GADA‐positive patients (4%, P  < 0.0001). Furthermore, over a 3 year monitoring period, F‐CPR levels decreased in ELISA‐GADA‐positive SPIDDM, whereas it was maintained in patients with RIA‐GADA alone, regardless of GADA affinity. Conclusions: These results suggest that bivalent ELISA for GADA is superior to the RIA method in diagnosing type 1 diabetes. Moreover, the diagnostic superiority of the ELISA‐GADA made possible the concurrent identification of SPIDDM patients at high‐risk of early progression, and allowed for more accurate clinical diagnosis and management. Abstract : The present study showed that bivalent ELISA for GADA is superior to the RIA method, not only in diagnostic performance of type 1 diabetes but also in identifying patients at high‐risk of early progression in SPIDDM. There was a statistically significant difference in F‐CPR among the four groups of SPIDDM ( P  = 0.04). The mean F‐CPR in patients with RIA + /ELISA + (−33.2 ± 9.5%) was significantly greater than that of patients who were positive for RIA‐GADA alone (2.6 ± 14.6%, P  < 0.05) and negative for both assays (13.3 ± 12.9%, P  < 0.05), but not so when compared with patients with ELISA‐GADA alone.